2021
DOI: 10.1038/s42003-020-01646-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing spectral quality with quantum dots to enhance crop yield in controlled environments

Abstract: Bioregenerative life-support systems (BLSS) involving plants will be required to realize self-sustaining human settlements beyond Earth. To improve plant productivity in BLSS, the quality of the solar spectrum can be modified by lightweight, luminescent films. CuInS2/ZnS quantum dot (QD) films were used to down-convert ultraviolet/blue photons to red emissions centered at 600 and 660 nm, resulting in increased biomass accumulation in red romaine lettuce. All plant growth parameters, except for spectral quality… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 40 publications
1
51
0
Order By: Relevance
“…Before making assumptions about the reasons for the positive effect of the PCF, it should be noted that the passing of light through glass coated with luminescent nanopar-ticles was not accompanied by a noticeable increase in the intensity of the visible range. However, in the present work, as well as in a number of other works, an increase in plant productivity was demonstrated [25][26][27][28][29][30][31][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Nanosized particles can act as a protectant against UV owing to their capability to absorb and scatter ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 68%
“…Before making assumptions about the reasons for the positive effect of the PCF, it should be noted that the passing of light through glass coated with luminescent nanopar-ticles was not accompanied by a noticeable increase in the intensity of the visible range. However, in the present work, as well as in a number of other works, an increase in plant productivity was demonstrated [25][26][27][28][29][30][31][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Nanosized particles can act as a protectant against UV owing to their capability to absorb and scatter ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, Gerovac et al [30] found greater fresh weight in mustard microgreens grown under red/green/blue (74/18/8%) compared to red/blue (87/13%) and red/blue/far-red (84/9/7%), while they did not find significant differences in the fresh weight of kohlrabi and mizuna microgreens. Light-absorbing film with peak emission at 600 or 660 nm induced 11% greater edible fresh mass in lettuce compared to no film [31]. In another study, the treatment of tomato transplants with supplementary light at 595 nm led to a decreased leaf area, and shoot and root dry weight compared to basal light [32].…”
Section: Morphologymentioning
confidence: 99%
“…This setup has 66 kW of identical enhanced bifacial red PV modules. In addition to the transmission percentage (Figure 1) for these crystalline silicon-based PV, the enhancements of red greenhouse modules have many other variables to optimize for, including testing the density, size and chemical makeup of nanoparticles responsible for the spectral shifting via fluorescence [131][132][133]. The interplay between the PV and these nanoparticles need to be investigated for each new crop.…”
Section: Case Study Of Red Agrivoltaic Module Experimental Design With a Poscasmentioning
confidence: 99%